Meta Analysis: The Effect of Realistic Mathematics Education (RME) on Students’ Mathematical Conceptual Understanding in Indonesia - Nurrahmah Nurrahmah; Muhammad Fachri B. Paloloang; Sukayasa Sukayasa (FKIP - Universitas Riau, 2026)
This study investigates the effect of Realistic Mathematics Education (RME) on students’ mathematical conceptual understanding in Indonesia by addressing inconsistent findings from previous studies. A meta-analysis was conducted through a Systematic Literature Review following PRISMA guidelines. Fourteen primary studies published between 2015 and 2025 were selected based on inclusion criteria, namely experimental or quasi-experimental studies involving Indonesian students and reporting sufficient statistical data. Effect sizes were calculated using Hedges’ g and analyzed with Comprehensive Meta-Analysis (CMA) version 4.0. Due to significant heterogeneity, a random-effects model was applied, while publication bias was examined using several bias detection methods. The findings revealed that RME had a large positive effect on students’ conceptual understanding, with an overall effect size of 1.225 (p < 0.05). Moderator analysis showed that the effectiveness of RME varied across educational levels, learning materials, and sample sizes, with the strongest effects found at the elementary school level and in geometry-related topics. No indication of publication bias was identified. These findings suggest that mathematics teachers should prioritize the implementation of RME, particularly in elementary mathematics and geometry learning, to promote more meaningful and contextual learning experiences.